2014
DOI: 10.1002/tox.21952
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances Chemosensitivity in Mouse Melanoma Model Through Connexin 43 Upregulation

Abstract: Although current studies indicate that resveratrol exhibits potential antitumor activities, the precise mechanisms of its beneficial effects combined with chemotherapy are not fully understood. This work is warranted to elucidate the underlying mechanism of antitumor effects by the combination therapy of resveratrol and cisplatin. The presence of functional gap junctions is highly relevant for the success of chemotherapy. Gap junctions mediate cell communication by allowing the passage of molecules from one ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…Resveratrol treatment enhanced cisplatin cytotoxicity in a mouse melanoma model, which was believed to occur through increased Connexin 43, a ubiquitous gap junction protein. 170 In another study, exposure of melanoma cells to resveratrol inhibited Ref-1-activated AP-1 DNA-binding and endonuclease activities, rendering melanoma cells more sensitive to dacarbazine treatment. 171 …”
Section: Phytochemicalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Resveratrol treatment enhanced cisplatin cytotoxicity in a mouse melanoma model, which was believed to occur through increased Connexin 43, a ubiquitous gap junction protein. 170 In another study, exposure of melanoma cells to resveratrol inhibited Ref-1-activated AP-1 DNA-binding and endonuclease activities, rendering melanoma cells more sensitive to dacarbazine treatment. 171 …”
Section: Phytochemicalsmentioning
confidence: 98%
“…170,193 Moreover, phytochemicals are remarkably nontoxic. The proposed mechanisms of these phytochemicals are yet to be fully elucidated, however, it has been proposed that due to their ubiquity in nature, through evolution, phytochemicals inherently possess diverse mechanisms of action.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…It is now suggested that treatment with resveratrol increases Cx43 gap-junction communication, as a knockdown of Cx43 resulted in a reduction of cell death after treatment with both cisplatin and resveratrol. Additionally the MAPK signaling pathway was activated, and the use of MAPK inhibitors also decreased the expression of Cx43 protein [244]. …”
Section: (4) Cell-cell Communication and Anticancer Treatmentmentioning
confidence: 99%
“…It has a protective effect against angiogenesis in breast cancer cells (25), but significantly increases tubulogenesis when glioma cells are co-cultured with human umbilical vascular endothelial cells (26). Some studies indicate that resveratrol increases Cx43 expression and GJ in cancer cells such as those of hepatocellular carcinoma (27) and melanoma (28). Akt is one of the resveratrolassociated predicted targets on colorectal cancer (29) and is regulated by Cx43 in many cases of antitumor studies.…”
Section: Discussionmentioning
confidence: 99%